المرسبة بطريقة التحلل الكيميائي الحراري(NiS)تحضير ودراسة الخصائص الفيزيائية لأغشية كبريتيد النيكل - تامة, دلال (جامعة الوادي University of Eloued, 2019)
" الهدف من عملنا هو تحضير شرائح كبريتيد النيكل Ni17S18)) وإيجاد المقادير المميزة لهذه الشريحة المحضره في هذه الدراسة تم تحضير أغشية رقيقة من كبريتيد النيكل (Ni17S18) المحضرة بطريقة الرش الكيميائي الحراري على ركائز زجاجية بدرجة حرارة 523˚k، حيث استعملنا محلول نترات النيكل ( Ni(NO3)2.6H2O) (مصدر للنيكل (Ni بتركيز مولى mol/l0.01 ومحلول ثوريا CS(NH2)2(مصدر للكبريت S) بتركيز مولى mol/l0.03. أظهرت نتائج انعراج الاشعة السينية أن الاغشية المحضرة ذات تركيب سداسي حسب البطاقة الدولية للقياسات JCPDS-98-003-7164والنمو المفضل للشريحة هو (301) أظهرت النتائج البصرية أن أغشية كبريتيد النيكل (Ni17S18) ذات نفاذية تصل إلى(% 4.36)، وانعكاسية تصل %8.5، وتملك فجوة طاقية في حدود ev1.24، كما أنها تمتاز بتوصيلة بصرية عالية تقدر ب s/1) 1013×8.54. أظهرت قياسات الاشعة تحت الحمراءFTIR بروز الرابطة Ni-S الموافقه للتردد cm-1603.12 "" The purpose of our work is to prepare nickel sulphide thin layer (Ni17S18) and find the specific parameters (optical and tructural) of this prepared thin layer. In this study, the nickel sulphide thin layer (Ni17S18) prepared by thermal chemical spraying were prepared on glass substrates at a temperature of 523˚k. Where, we used nickel nitrate solution (Ni (NO3)2 .6H2O) (as nickel source Ni) with molar concentration of 0.01 mol/l and solution of thiorea CS (NH2) 2 (as sulfur source S) with molar concentration of 0.03 mol/l.. The results of the X-ray diffraction showed that the prepared thin layer are hexagonal according to the international standard of measurements JCPDS-98-003-7164 and the preferred growth of the slice is (301). The optical results showed that the nickel sulfide thin layer (Ni17S18) have a permeability of 4.36%, reflectivity of 8.5%, an energy gap of 1.24 eV, and have a high optical conductivity of 8.542× 1013(1/s). For FTIR infrared measurements the results showed Ni-S bonding at the frequency of 603.12 cm-1. "" The purpose of our work is to prepare nickel sulphide thin layer (Ni17S18) and find the specific parameters (optical and tructural) of this prepared thin layer. In this study, the nickel sulphide thin layer (Ni17S18) prepared by thermal chemical spraying were prepared on glass substrates at a temperature of 523˚k. Where, we used nickel nitrate solution (Ni (NO3)2 .6H2O) (as nickel source Ni) with molar concentration of 0.01 mol/l and solution of thiorea CS (NH2) 2 (as sulfur source S) with molar concentration of 0.03 mol/l.. The results of the X-ray diffraction showed that the prepared thin layer are hexagonal according to the international standard of measurements JCPDS-98-003-7164 and the preferred growth of the slice is (301). The optical results showed that the nickel sulfide thin layer (Ni17S18) have a permeability of 4.36%, reflectivity of 8.5%, an energy gap of 1.24 eV, and have a high optical conductivity of 8.542× 1013(1/s). For FTIR infrared measurements the results showed Ni-S bonding at the frequency of 603.12 cm-1. "
مذكرة ماستر تخصص فيزياء
Keywords: الكلمات المفتاحية :أغشية رقيقة – كبريتيد النيكل (NiS) – انعراج الاشعة السينية - FTIR; Thin layers - Nickel sulphide (NiS) - X-ray diffraction - FTIR